2021
DOI: 10.1007/s11356-021-14710-y
|View full text |Cite
|
Sign up to set email alerts
|

Ex situ phytoremediation trial of Sardinian mine waste using a pioneer plant species

Abstract: The mitigation of metals contamination is currently a crucial issue for the reclamation of mine sites. Indeed, mine wastes are often disposed in open dumps and consequently pollutants are subjected to dispersion in the surrounding areas. In this study, the potential use of Helichrysum microphyllum subsp. tyrrhenicum for phytostabilization was evaluated in ex situ conditions. Ninety specimens were randomly selected and were planted in three substrates (reference substrate, mine waste materials, and mine wastes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…tyrrhenicum is the dominant plant. According to the plant survival rate and plant growth index, it was confirmed that the dominant plants were more adaptable to the polluted substrate [14]. Another study screened out plants suitable for ecosystem restoration by comparing the tolerance and performance indices of plants to further promote ecological restoration [15].…”
Section: Introductionmentioning
confidence: 99%
“…tyrrhenicum is the dominant plant. According to the plant survival rate and plant growth index, it was confirmed that the dominant plants were more adaptable to the polluted substrate [14]. Another study screened out plants suitable for ecosystem restoration by comparing the tolerance and performance indices of plants to further promote ecological restoration [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the growth environment in mining areas characterized by a large heterogeneity of the substrate has a great influence on the effect of phytoremediation and there are basic science knowledge gaps related to the potential of plants in phytoremediation of mining dumps. For the growth of most plant species, sterile dumps are limiting environments due to unfavorable conditions related to the properties of the substrates like low levels of nutrients (K, N, P) and organic matter, significant amounts of heavy metals, and poor structure 24 . Therefore, the improvement of plant growth conditions by amendments and by treatments (fertilizers) to create larger nutrient concentration, larger water retention capacity, and an improved macrobiotic community in the root areas have been listed among complementary remediation strategies to phytoremediation 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the improvement of plant growth conditions by amendments and by treatments (fertilizers) to create larger nutrient concentration, larger water retention capacity, and an improved macrobiotic community in the root areas have been listed among complementary remediation strategies to phytoremediation 25 . Furthermore, mixing the sterile material with unpolluted soil, compost, or organic wastes like dewatered sludge resulting from sewage treatment plants to positively influence plant growth, achieve better plant nutrient statuses, and modify the physical–chemical properties of mine substrates have also been reported in studies of soil and tailing dams 24 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of Sardinia for the European mining industry until the XX th century and several As contamination hot spots are nowadays still recognizable among the island ( Ardau et al., 2008 ; Cidu and Biddau, 2007 , Cidu et al., 2005 ; Cidu and Fanfani, 2002 ; Frau et al., 2005 , 2008 ), no studies concerning As phytoremediation were carried out. Nevertheless, in the last two decades, different native taxa were found tolerant to metals like Zn and Pb (e.g., Bacchetta et al., 2012 , 2015 , 2017 , 2018 ; Boi et al., 2020a , 2020b , 2021 ; Cao et al., 2004 ; Concas et al., 2015 ; De Giudici et al., 2015 , 2017 ; Jiménez et al., 2005 , 2011 , 2014 , 2021 ; Medas et al., 2015 , 2017 ). In the last years, more of the efforts were spent investigating H. microphyllum subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is an indifferent edaphic species that grows on a wide altitudinal range. This approach has pointed out its ability to tolerate heavy concentrations of Zn and Pb, storing them in the hypogean organs and behaving as excluder species ( Bacchetta et al., 2017 , 2018 ; Boi et al., 2020b , 2021 ; Cao et al., 2004 ). Furthermore, ecophysiology of seed germination studies pointed out that seeds can germinate under very high concentrations of Zn and Pb, without the complete inhibition of the process ( Boi et al., 2020a ).…”
Section: Introductionmentioning
confidence: 99%